Odpowiedź:
1a) -8[tex]x^{2}[/tex] + 5x - 1/2 = 1/2 -x
-8[tex]x^{2}[/tex] + 6x - 1 = 0
delta = b² - 4ac
delta = 36 - 4 × (-8) × (-1)
delta = 4 x1= (-6 + 2) ÷ (-16) = 1/4
√4=2 x2= (-6 - 2) ÷ (-16) =1/2
1b) -20x² - 11x +3 = 0
delta = 121 - 4 × (-20) × 3
delta = 361 x1= 11 - 19 / (-40) = 0,2
√361=19 x2= 11 + 19/ (-40) = -0,75
2a) 16x²-8x+1 = x+2-4x²-8x
20x²-x-1=0
delta= 1 - 4 ×20×(-1)
delta= 81 x1= 1-9÷40 = -0,2
√81=9 x2= 1+9/40 = 0,25
2b) 9-4x²=12x-3+8x²-2x
-12x²-10x+12=0
delta= 100 - 4×(-12) ×12
delta= 676 x1= 10+26/(-24) = - 3/2
√676=26 x2= 10-26/(-24)= 2/3
2c) 1-4x+4x²= 9x²+12x+4
-13x²-16x-3=0
delta= 256 - 4×(-13) ×(-3)
delta= 100 x1= 16 +10/(-26)= -1
√100= 10 x2= 16-10/(-26) = - 3/13
Szczegółowe wyjaśnienie: